Women’s business survival: challenges and strategies for single mother entrepreneurs / Salmah Topimin, Noor Fzlinda Fabeil and Ahmad Shakani Abdullah - Topimin, Salmah; Fabeil, Noor Fzlinda; Abdullah, Ahmad Shakani (Universiti Teknologi MARA, Cawangan Melaka, 2019)
The entrepreneurial experience of single mother entrepreneurs remains largely unexplored. This paper addresses this issue by investigating the strategies used by single mother entrepreneurs in ensuring the survival of their businesses. The data for this study was collected based on a qualitative approach. An in-depth interviews were conducted with 27 single mother entrepreneurs who operate their entrepreneurial activities in Kota Marudu, Sabah. The findings revealed that the main challenges faced by the majority of the single-mother entrepreneurs in this study were closely related to the lack of entrepreneurial skills and business resources, the issue of stigmatisation by society as well as issue in balancing their domestic and business responsibilities. To ensure the survival of their businesses, single mother entrepreneurs are mostly dependent on their informal support system and inner strengths. Although useful, the informal support system is unable to support the business survival of their businesses and strengthen their personal financial position.